Macroeconomic policy interaction: State dependency and implications for financial stability in UK: A systemic review - Muhammad Ali Nasir; Junjie Wu; Milton Yago; Alaa M. Soliman (Cogent Business & Management, 2016)
The association between economic and financial stabilities and influence of macroeconomic policies on the financial sector creates scope of active policy role in financial stability. As a contribution to the existing body of knowledge, this study has analysed the implications of macroeconomic policy interaction/coordination for financial stability, proxied by financial assets, i.e. equity and bonds price oscillation. The critical review and analysis of the existing literature on the subject suggests that there is also ample evidence of interdependence between monetary and fiscal policies and this interrelation necessitates coordination between them for the sake of financial stability. There is also a case for analysing the symmetry of financial markets responses to macroeconomic policy interaction. On methodological and empirical grounds, it is vital to test the robustness of policy recommendations to overcome the limitation of a single empirical approach (Jeffrey–Lindley's paradox). Hence, the Frequentist and Bayesian approaches should be used in commentary manner. The policy interaction and optimal policy combination should also be analysed in the context of institutional design and major financial events to gain insight into the implications of policy interaction in the periods of stable economic and financial environments as well as period of financial and economic distress.
Keywords: 650